Effect of ultrafiltered fractions from casein on lactic acid biosynthesis and enzyme activity in yoghurt starter cultures. (14th March 2013) - Zhang, Qingli; Brashears, Mindy M.; Yu, Zhimin; Ren, Jiaoyan; Li, Yinjuan; Zhao, Mouming
Summary In this work, five ultrafiltered fractions (UFs) with molecular mass less than 3 kDa (kilo‐daltons) from casein hydrolysates treated with alcalase, flavourzyme, neutrase, papain and trypsin, respectively, were obtained. The effect of five UFs on the fermentation for lactic acid (LA) production by mixed cultures of Streptococcus thermophilus (St) and Lactobacillus delbrueckii subsp. bulgaricus (Lb) during 72 h of cultivation was investigated. Compared with the control, LA production was, respectively, enhanced by 23.66%, 39.01%, 29.74%, 49.64% and 47.40% with the supplement of UF‐A, UF‐F, UF‐N, UF‐P and UF‐T at 24 h. The possible mechanism of LA production enhanced was elucidated by the time course analysis of the specific activity of glucokinase, phosphoglucose isomerase, 6‐phosphofructokinase, pyruvate kinase and lactate dehydrogenase during fermentation process. In addition, the results obtained showed the diverse influence of five UFs on the bacterial fermentation was attributed to their different amino acid distribution.